(untitled) (Brazilian Journal of Radiation Sciences, 2022)
All biota is exposed to natural radiation, the soil being the major source of radionuclides. Phosphogypsum is classified as a NORM residue of the phosphate fertilizer industry, often used in agriculture, as a soil conditioner. This residue is stored in stacks by the phosphate industries, potentially posing environmental risks. The aim of this study is to compare the risk for the terrestrial and aquatic biota arising from the storage of PG residue in the environment with that arising from its reuse as soil amendment. For this purpose, typical Brazilian soils amended with PG and PG itself were leached with distilled water. The concentration of natural radionuclides in the soil samples were used to evaluate the risk for terrestrial and aquatic biota, using the ERICA Tool. The results for terrestrial biota exposed to soils amended with phosphogypsum showed a risk reduction of about 85%, when compared to the exposure arising from phosphogypsum stacks. Considering the aquatic biota, the results showed a risk reduction of about 46% when comparing to radionuclide concentrations in leachates from phosphogypsum and from the soils amended with phosphogypsum. A new risk reduction assessment was performed to determine exclusively the contribution of the application of PG to the soil using the soil without PG, the risk reduction for terrestrial biota was of 99% and aquatic biota was a 74% reduction. Finally, it can be concluded that the addition of phosphogypsum in soils reduces the risk quotient related to the exposure of terrestrial and aquatic biota, showing that this is a safe practice.